2009
DOI: 10.1093/mp/ssp014
|View full text |Cite
|
Sign up to set email alerts
|

Control of PHERES1 Imprinting in Arabidopsis by Direct Tandem Repeats

Abstract: Genomic imprinting is an epigenetic phenomenon that causes monoallelic expression of specific genes dependent on the parent-of-origin. Imprinting of the Arabidopsis gene PHERES1 requires the function of the FERTILIZATION INDEPENDENT SEED (FIS) Polycomb group complex as well as a distally located methylated region containing a tandem triple repeat sequence. In this study, we investigated the regulation of the close PHERES1 homolog PHERES2. We found that PHERES2 is also a direct target gene of the FIS Polycomb g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
66
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 32 publications
6
66
0
Order By: Relevance
“…Whereas HDG8 and HDG9 are predominantly maternally expressed, HDG3 is expressed from the paternal allele. Therefore, in agreement with previous findings (Makarevich et al, 2008, Villar et al, 2009), demethylation of transposons or repeat sequences of the maternally inherited alleles can result in imprinted expression with the paternal allele being expressed. Gehring et al (2009) suggest that the best candidates for imprinted genes are those that are less methylated in the endosperm than in the embryo, show endospermpreferred expression and are transcribed at low levels in other parts of the plant.…”
Section: Imprinting Mechanismssupporting
confidence: 93%
“…Whereas HDG8 and HDG9 are predominantly maternally expressed, HDG3 is expressed from the paternal allele. Therefore, in agreement with previous findings (Makarevich et al, 2008, Villar et al, 2009), demethylation of transposons or repeat sequences of the maternally inherited alleles can result in imprinted expression with the paternal allele being expressed. Gehring et al (2009) suggest that the best candidates for imprinted genes are those that are less methylated in the endosperm than in the embryo, show endospermpreferred expression and are transcribed at low levels in other parts of the plant.…”
Section: Imprinting Mechanismssupporting
confidence: 93%
“…Maternal demethylation of tandem repeats downstream of PHE1 is also thought to be required for maternal PHE1 silencing. This idea is supported by the observation that loss of methylation in the paternal genome because of a met1 mutation reduced expression of the paternal PHE1 allele (17,20). Indeed, we detected DME-dependent endosperm hypomethylation of these tandem repeats (33) (Fig.…”
Section: Effects Of Paternal Met1 and Maternal Dme And Fie Mutations Onsupporting
confidence: 69%
“…3B). Thus, the current model explaining regulation of PHE1 imprinting proposes that maternal DNA demethylation near the gene exposes a PRC2 binding site, thereby allowing PcG-mediated silencing of the maternal allele (17). Supporting this model, Weinhofer et al (40) recently reported that DNA hypomethylation allows targeting by PcG proteins in endosperm.…”
Section: Effects Of Paternal Met1 and Maternal Dme And Fie Mutations Onmentioning
confidence: 96%
See 2 more Smart Citations